Generalidades históricas de contemporaneidad en la dimensión social-valorativa y jurídica del Medio Ambiente. - Antúnez Sánchez, Alcides Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This work has as end demonstrate that the problematic environmental keeps more effective than never, being in danger with the negative actions of the more rich countries and developed of the world the disappearance of the in any way whatever social man and with it of the earth planet, to continue with this type of aggresive conduct to the halfback it gives atmosphere. It has concluded the first decade of the XXI century and is not watched changes, in spite of the diverse meetings at international level that have been carried out, and the voice of several statesmen, between those who is highlighted the reflections of the Dr. Fidel Castro, about urging to the Great powerses to modify your conducts for the sake of preserving the human species. It have used to shape this monograph the methods of bibliographical revision in doctrinal and normative juridical matter of international cut, departing from your social dimension until the juridical context, and the axiological method.
Keywords: halfback gives atmosphere; environmental problems; social dimension; |valorativa|; environmental conscience; cultivates juridical environmental; ecology; |biodiversidad|